Study on a class of Schrödinger elliptic system involving a nonlinear operator - Wang, Guotao; Yang, Zedong; Agarwal, Ravi P.; Zhang, Lihong (Nonlinear Analysis: Modelling and Control, 2020)
This paper considers a class of Schrödinger elliptic system involving a nonlinear operator. Firstly, under the simple condition on and ’, we prove the existence of the entire positive bounded radial solutions. Secondly, by using the iterative technique and the method of contradiction, we prove the existence and nonexistence of the entire positive blow-up radial solutions. Our results extend the previous existence and nonexistence results for both the single equation and systems. In the end, we give two examples to illustrate our results.